Kakšne so predstave odraslih v Sloveniji o starosti in starejših osebah? - Zupančič, Maja (Kakovostna starost, 2011)
The article presents findings of two Slovene studies. The first one investigated knowledge about the facts of aging and elderly as well as negative and positive stereotypes about the elderly in a sample of adults of different ages (N=822). The second study explored changes in university students' knowledge and stereotypes about the elderly after attending a course in developmental psychology. A relatively poor knowledge of facts aboutaging and characteristics of the elderly was revealed. Negative stereotypes about the elderly clearly prevailed over positive stereotypes. The highest proportion of misconceptions was displayed in the domain of mentalhealth and psychological functioning of the elderly but the physical changes in the old age were recognized quite acurately. The participants' education was consistently related to their knowledge about aging and the elderly, and to lower presence of negative stereotypes. The elderly participants as compared to the younger respondents also held misconceptions about mental health in the old age more frequently. The second study demonstrated a significant positive effect of the study course on students' knowledge about the old age, especially in the domain of psychological functioning and mental health of the elderly. Moreover, the students' negative beliefs about the elderly decreased significantly.
Keywords: stari ljudje; staranje; stališča; stereotipi